2018
DOI: 10.1002/adem.201800520
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth of Lithium–Silicon Alloy on Crystalline Silicon

Abstract: Si is an attractive material for anodes in Li ion batteries because of high specific capacity. However, it undergoes significant volume change during electrochemical reactions, causing mechanical fractures and capacity decay, which is a serious bottleneck for commercialization. Despite several research attempts to understand the stress evolution in Si, the process remains unclear. A fundamental study of the initial formation of the Li–Si alloy is hence necessary for a better understanding of the stress evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…With both electrodes, the faint potential well in the discharge curve of the first cycle is likely due to the passivating nature of the polymeric binder coating the silicon. However, a similar phenomenon has also been described with crystalline silicon, as well as with other alloy anodes which are known to require an overpotential to nucleate the lithiated phase during the initial stages of Li-alloy formation [34][35][36][37] The relationship between the nano silicon synthesis, crystallinity, and electrochemical performance with aqueous binders is the subject of ongoing work.…”
Section: Resultsmentioning
confidence: 73%
“…With both electrodes, the faint potential well in the discharge curve of the first cycle is likely due to the passivating nature of the polymeric binder coating the silicon. However, a similar phenomenon has also been described with crystalline silicon, as well as with other alloy anodes which are known to require an overpotential to nucleate the lithiated phase during the initial stages of Li-alloy formation [34][35][36][37] The relationship between the nano silicon synthesis, crystallinity, and electrochemical performance with aqueous binders is the subject of ongoing work.…”
Section: Resultsmentioning
confidence: 73%
“…Furthermore, and in contrast to solid electrolyte composed silicon electrodes, silicon wafers are stable in ambient conditions, which would avoid the need for specialized facilities to maintain dry conditions during solid state anode fabrication. Several previous studies have reported the fundamental mechanisms of electrochemical lithium insertion in silicon wafers in liquid electrolyte systems. However, in this study, we report on the outstanding performance of silicon wafer cells in solid electrolyte systems, achieving an increased cycle retention of up to 100 cycles by controlling the surface morphology. Additionally, we have successfully operated a full-cell with a Ni-rich NCM cathode.…”
mentioning
confidence: 78%
“…Although amorphous Si exhibits isotropic expansion along its original morphology with the Li-alloying reaction, directionally anisotropic volume expansion also occurs during the lithiation of crystallographically oriented Si as the resulted form of Li x Si. Previous research has shown that the lithiated morphology of crystalline Si is affected by the crystalline orientation (e.g., ⟨100⟩, ⟨110⟩, and ⟨111⟩). Si nanopillars (SiNPs) can be a distinct model for visualizing the anisotropic volume expansion of nanosized Si with a cylindrical morphology. ,, SiNP volume expansion favors the crystal orientation of lithium insertion and affects the fracture locations, which are generated between the expanded orientations. According to the failure model of lithiation reaction of silicon, fractures occur due to large compressive stress at the interface between silicon core and amorphous lithium silicate when the Si anode undergoes the two-phase reaction during the first charge/discharge cycle …”
mentioning
confidence: 99%